Potential cancer risk associated with CT scans: Review of epidemiological studies and ongoing studies. (September 2015) - Bernier, Marie-Odile; Journy, Neige; Baysson, Hélène; Jacob, Sophie; Laurier, Dominique
Abstract: Introduction: The increasing use of computed tomography (CT) scans in paediatric population raises the question of a possible health impact of ionizing radiation exposure associated with CT scans. Material and methods: Three cohort studies have been recently published that have assessed the risk of cancer related to CT examinations of children and young adults. The methodology and results of these studies are presented, as are ongoing studies and the perspectives they provide. Results: The UK cohort included over 176, 000 young people, who underwent one or more CT scans between 1985 and 2002. The Australian study compared the risk of cancer and leukaemia in a population of 680, 000 young people exposed to CT scans between 1985 and 2005 to non-exposed people of similar ages. The third study, from Taiwan, compared the risk of malignant or benign brain tumour in a cohort of 24, 418 children exposed to CT scans under 18 years of age between 1998 and 2006 to non–exposed people of similar ages. The British and Australian studies showed a significant dose–response relation between the exposure to CT and leukaemia or brain tumour. These results are consistent with predictions from A-bomb survivors' data. The Taiwanese study failed to show an overall increased risk of cancer, but observed that the risk of benign brain tumour was significantly increased. However, uncertainties in dosimetric estimation and potential bias linked to underlying medical conditions should be considered. Conclusion and perspectives: Further studies with more accurate dosimetry and assessment of potential bias and uncertainties are needed. Ongoing national studies and the European collaborative EPI-CT study will help to better understand the relation between low-level radiation exposure and cancer and to support recommendations for patients' radiation protection. Highlights: CT scans are associated with much higher doses of radiation than radiographies. Two recent epidemiological studies focused on exposure to CT in childhood. An increased risk of leukaemia and brain tumour was shown for doses <100 mSv. The results are consistent with predictions from A-bomb survivors' data. Potential bias linked to the CT's indication could not be ruled out.